1995
DOI: 10.1143/jjap.34.177
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Refractive Index of Porous InP Fabricated by Anodization of (111)A Surface

Abstract: We measured, for the first time, the anisotropic refractive index of porous InP obtained by photoassisted anodization of the (111)A surface in the direction parallel (n o=2.82) and perpendicular (n e=2.66) to the axis of the pores. The refractive index in the two directions was found to be 10–20% lower than the refractive index of bulk InP (n=3.17).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 1 publication
1
24
1
Order By: Relevance
“…This surface exhibited a porous structure involving oxide components. Further study revealed that a porous (100) InP structure similar to that reported for the (111) InP surface [6][7][8][9] is formed in this passive region of the overpotential as discussed elsewhere 12) . XPS studies were also carried out on the anodically processed surfaces of n-InP in order to further confirm the presence of active-passive transition.…”
Section: Surface Morphology and Xps Studysupporting
confidence: 69%
See 1 more Smart Citation
“…This surface exhibited a porous structure involving oxide components. Further study revealed that a porous (100) InP structure similar to that reported for the (111) InP surface [6][7][8][9] is formed in this passive region of the overpotential as discussed elsewhere 12) . XPS studies were also carried out on the anodically processed surfaces of n-InP in order to further confirm the presence of active-passive transition.…”
Section: Surface Morphology and Xps Studysupporting
confidence: 69%
“…In the literature, only limited works [2][3][4][5] have been reported on the anodic etching of InP, and their etch rate and uniformity have not been clarified. More recent anodization experiments [6][7][8][9] on InP using HCl electrolyte have led to the formation of InP porous structures. Although such an anodization mode is interesting for the formation of quantum structures and photonic crystals, it is not suitable for uniform etching.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a maximum depth of about 80 μm was achieved by anodization for 3 min. This value is much larger than the value reported for porous layers made on (111)A n-InP surfaces which had a maximum depth of 30 μm [25][26][27].…”
Section: (A)-(d)contrasting
confidence: 59%
“…On the other hand, formation of <111>-oriented straight pores without branches were reported by Takizawa et al for (111) oriented n-InP [25][26][27].…”
Section: 1)formation Of Nanoporesmentioning
confidence: 84%
“…For III -V compound semiconductors such as GaAs [2 -4], InP [5][6][7][8][9][10][11] and InSb [12], formation of porous layers and their many different properties as compared to the bulk materials have also been investigated.…”
Section: Introductionmentioning
confidence: 99%